Variations of the chemical components and biological activities of Thymus capitatus essential oil from three regions in Palestine - Nidal Jaradat; Alaa Barkat; Ahmad Khasati; Murad Abualhasan (Scientific Reports)
Abstract Thymus capitatus is a widely utilized medicinal plant in Palestine. The main goal of this study was to assess the phytochemical content of T. capitatus essential oils (EOs) from three Palestinian regions using hydro-distillation. Furthermore, the EO extracted from the plant was subjected to biological tests. GC-MS spectrometry was used to identify and quantify the elements in the EOs examined. The DPPH assay and the β-carotene-linoleic acid assay were utilized to determine the levels of antioxidant activity. The plant’s anti-lipase activity was carried out using a pancreatic lipase inhibition assay. α-amylase inhibitory activity of the EOs samples was studied compared with the hypoglycemic drug, Acarbose. An antimicrobial assay was conducted against seven common bacteria and fungi types. Additionally, Hep-G2 cells were used to assess the anticancer activity. The EO components were mainly monoterpenes, thymol, and carvacrol. Chemical components of the EOs varied between districts (Ramallah: carvacrol (31.25%), γ-terpinene (30.94%), Jenin: γ-terpinene (67%), cis-b-terpineol (12.91%), Hebron: thymol (40.35%), b-Caryophyllene (13.23%) were the main components of the EOs in the districts. The antioxidant activity of T. capitatus EOs was shown to be dose-dependent. The results showed that the three districts had nearly the same IC50, a fourth-fold of gallic acid. The Hebron sample of T. capitatus EO showed antibacterial activity with MIC values between 0.1953 and 1.5625 µg/mL. All samples showed anti-lipase activity higher than Orlistat at concentrations equal to or above 200 µg/ml. Furthermore, all three EO samples inhibited α-amylase concentration-dependently. All samples showed promising cytotoxicity results against Hep-G2, with an average percent inhibition of 85% at a concentration of 62.5 µg/mL. The chemical composition of the EO of T. capitatus is related to the plant’s origin, soil components, genetic variables, and climatic conditions, which in turn reflect the plant’s biological activity.